The Interaction of AFB1 Aflatoxin and Lactococcin A; Molecular Docking - Özgen, Arzu; Ünlü, Nihan; Canbay, Canan Aksu (Sakarya University, 2024)
Aflatoxins (AF), which cause diseases in humans and animals, are mycotoxins produced by certain types of fungi. Bacteriocins are natural antimicrobial substances synthesized by bacteria. These substances that are in protein structure, generally have short chain and small molecular weight. According to the classification made by Klaenhammer, especially considering Gram (+) bacteria, bacteriocins are divided into 4 different classes. These are Class I (Class IA, Class IB), Class II (Class IIA, Class IIB, Class IIC, Class IID), Class III and Class IV. Enterocin A, Sakacin A, Lactococcin A can be given as examples of Class II bacteriocins. In this study, we examined the interaction of AFB1 aflatoxin (ligand) and Lactococcin A (protein) bacteriocin, which is in Class II, using Molecular Docking. The results showed that Lactococcin A molecule have the potential to be used for aflatoxin degradation. © 2024, Sakarya University. All rights reserved.
Keywords: Aflatoxins (AF); Bacteriocins; Lactococcin A; Molecular docking